DINAMIKA MODERNISASI PERTANIAN PADI DI KECAMATAN REJOSO, KABUPATEN NGANJUK - Wiradarma, Rahadyan; Idris, Idris; Ratnawati, Nurul (Universitas Negeri Malang, 2024)
Rejoso as a rice producing region needs to modernize rice farming. This modernization is expected to increase the efficiency of planting on land so that production costs can be reduced. The development of the use of rice transplanter planting machines has not met expectations because farmers are more interested in non-rice transplanter planting services. With this gap, the dynamics of modernization of rice farming, especially the use of rice transplanters in Rejoso District, is very interesting to research. Basically, modernization of rice farming includes seeding, land processing, planting and harvesting. This research focuses on modernizing rice farming using rice transplanter planting machines. This research is a descriptive qualitative research type of case study. The data sources used are primary and secondary data sources. The data taken are verbal words. The data collection techniques for this research are observation, interviews and documentation. The data analysis technique uses the interactive model from Miles and Huberman. The results of the research are: 1) The use of rice transplanter planting machines in Rejoso District is less effective; 2) Rice transplanter planting machines are not always suitable for all rice farming land; 3) Based on indicators of failure, modernization of rice planting using rice transplanter planting machines in Rejoso District, Nganjuk failed; 4) This failure of modernization is a failure of the government, rice translator planting service providers, and farmers; 5) Rational choice theory is used by actors (farmer) by considering advantages and disadvantages so that they can use resources efficiently; 6) Failure is influenced by external factors, namely the failure to achieve the goals of managers and farmers, competition, lack of progress or stagnation, as well as farmers' low interest in rice transplanters; 7) The results of this research can have implications for education, namely providing variety and enrichment of material about economic behavior in agricultural sector. Rejoso sebagai wilayah produsen padi perlu modernisasi pertanian padi. Modernisasi ini diharapkan mampu meningkatkan efisiensi penanaman di lahan sehingga biaya produksi dapat ditekan. Dalam perkembangan penggunaan mesin tanam rice transplanter tidak sesuai harapan karena petani lebih berminat pada jasa tanam nonrice transplanter. Dengan kesenjangan itu, dinamika modernisasi pertanian padi khususnya penggunaan alat tanam rice transplanter di Kecamatan Rejoso ini sangat menarik untuk diteliti. Pada dasarnya modernisasi pertanian padi mencakup pembibitan, pengolahan lahan, penanaman, dan pemanenan. Penelitian ini fokus pada moderenisasi pertanian padi dengan menggunakan mesin tanam rice transplanter. Penelitian ini merupakan penelitian kualitatif deskriptif jenis studi kasus. Sumber data yang digunakan sumber data primer dan sekunder. Data yang diambil adalah kata-kata verbal. Teknik pengumpulan data penelitian ini adalah observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan model interaktif dari Miles dan Huberman. Hasil penelitian, yaitu: 1) Penggunaan mesin tanam rice transplanter di Kecamatan Rejoso kurang efektif; 2) Mesin tanam rice transplanter tidak selalu cocok untuk semua lahan pertanian padi; 3) Berdasarkan indikator kegagalan modernisasi modernisasi penanaman padi dengan menggunakan mesin tanam rice transplanter di Kecamatan Rejoso, Nganjuk gagal; 4) Kegagalan modernisasi ini merupakan kegagalan pemerintah, penyedia jasa tanam rice transplater, dan petani; 5) Teori pilihan rasional digunakan aktor (petani) dengan mempertimbangkan kelebihan dan kekurangan sehingga dapat menggunakan sumberdaya secara efisiensi; 6) Kegagalan dipengaruhi oleh faktor eksternal, yaitu ketidaktercapaian tujuan pengelola dan petani, persaingan, ketiadaan kemajuan atau kemandegan, serta minat petani terhadap rice transplanter yang rendah; 7) Hasil penelitian ini, dapat berimplikasi bagi pendidikan yaitu memberikan variasi dan pengayaan materi tentang perilaku ekonomi dalam bidang pertanian.